Unsteady Flow of Chemically Reacting Nanofluid over a Cone and Plate with Heat Source/Sink - Basha, H. Thameem; Singh, Amandeep; Makinde, Oluwole Daniel; Arora, Akshay; Sivaraj, R. (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2018)
The intention of this communication is to explore the characteristics of Lorentz force on the fluid transport properties of a chemically reacting nanofluid with two types of geometries. Simulations have been done to investigate the controlling equations utilizing Crank-Nicolson scheme. Influence of embedded parameters such as Hartman number, heat source/sink, Brownian diffusion, chemical reaction parameter and thermophoretic diffusivity is graphically presented. Tables demonstrate the significant impact of sundry parameters on skin-friction factor, heat and mass transfer rates. The achieved results expose that the Hartman number having high influences on the fluid flow and heat transfer characteristics.